GREENHOUSE HEATING SYSTEMS BASED ON GEOTHERMAL ENERGY - Alijonov Xabibullo Avazbek o’g’li; Fayzullayev Zafarbek Farxod o’g’li; Jo’raboyev Mashhurbek Yaqubbek o’g’li; Muxammad Aminov Abrorbek Dilshodbek o‘g‘li (European Science Publishing, 2024)
Geothermal energy is one of the most important energy resources for electricity generation and is also used directly in heating, food and agriculture, aquaculture and some industrial processes. This paper presents a design of a greenhouse using a renewable energy resource for the thermal heating and electrical requirements for its operation. Photovoltaic , wind and geothermal energy are used for improve efficiency of crop production. In Egypt, the Suez Gulf is rich of geothermal springs. Ras Sedr is the site under consideration for chilli production, the required temperature is between 25-35 oC. There are several methods for greenhouse heating systems using geothermal energy which are finned pipe, standard unit heaters, low temperature unit heaters, fan coil units, soil heating, and bare tube. The economic analysis of thermal and electrical is done. The PV-wind hybrid system is proposed for greenhouse heating system which contains of (0.5 kW) photovoltaic arrays, (6 kW) wind turbines, one battery storage, inverter and charge regulator subsystems with levelized cost of energy of 0.114 $/kWh.[1]
Keywords: Agriculture, geothermal energy, heating system photovoltaic, renewable energy.